Ответ:
1) 6
2) 5
3) 7
4) -3
5) 3 17
6) 5
7) x = -11/3 x = 1
8) -12
9) sqrt((2 - 5 x)^2) = -3
10) 4
Пошаговое объяснение:
1) |m| + 4 = 10
|m| = 6
sqrt(m^2) + 4 = 10 ( sqrt - это корень) т.е корень из m^2!!!
m = 6
2) 6 - |x| = 2
|x| = 4
6 - sqrt(x^2) = 2
x = 4
3) |x - 3|= 4
sqrt((x - 3)^2) = 4
x = 7
4) |x+7|=4
sqrt((x + 7)^2) = 4
x = -3
5) |10-x|=7
|x-10|=7
sqrt((10 - x)^2) = 7
x = 3
x = 17
6) |x|=5
sqrt(x^2) = 5
х = 5
7) |3x+4|=7
sqrt((3 x + 4)^2) = 7
x = -11/3
x = 1
8) |1/3x+4|=0
|x/3 + 4|=0
x + 12 = 0
sqrt((x/3 + 4)^2) = 0
x = -12
9) |2-5x|=-3
sqrt((2 - 5 x)^2) = -3
10) - |3x-1| = -11
|1 - 3х| = 11
-sqrt((3 x - 1)^2) = -11
- |1 - 3х| = -11
x = -10/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) 6
2) 5
3) 7
4) -3
5) 3 17
6) 5
7) x = -11/3 x = 1
8) -12
9) sqrt((2 - 5 x)^2) = -3
10) 4
Пошаговое объяснение:
1) |m| + 4 = 10
|m| = 6
sqrt(m^2) + 4 = 10 ( sqrt - это корень) т.е корень из m^2!!!
m = 6
2) 6 - |x| = 2
|x| = 4
6 - sqrt(x^2) = 2
x = 4
3) |x - 3|= 4
sqrt((x - 3)^2) = 4
x = 7
4) |x+7|=4
sqrt((x + 7)^2) = 4
x = -3
5) |10-x|=7
|x-10|=7
sqrt((10 - x)^2) = 7
x = 3
x = 17
6) |x|=5
sqrt(x^2) = 5
х = 5
7) |3x+4|=7
sqrt((3 x + 4)^2) = 7
x = -11/3
x = 1
8) |1/3x+4|=0
|x/3 + 4|=0
x + 12 = 0
sqrt((x/3 + 4)^2) = 0
x = -12
9) |2-5x|=-3
sqrt((2 - 5 x)^2) = -3
10) - |3x-1| = -11
|1 - 3х| = 11
-sqrt((3 x - 1)^2) = -11
- |1 - 3х| = -11
x = -10/3
x = 4